US-Japan Security Alliance Adrift? - Akaha, Tsuneo (Mongolian Journal of International Affairs, 2015)
How stable is the US-Japan security alliance in the post-Cold War era? Have the “end of history”, the “end of the Cold War”, the end of a “hegemonic world”, and the “end of geography” (or the beginning of a borderless world economy) so altered the national security needs and priorities of the United States and Japan that they no longer need or desire the security alliance they have maintained since 1952? Will the alliance remain the anchor of Japanese and US policies in the Asia-Pacific region? In the age of multilateralism, will the two countries seek multilateral alternatives that will replace the bilateral alliance? In this brief analysis, I will review the ongoing debate in Japan and in the United States concerning the future of the US-Japan security alliance in the post-Cold War era. DOI: http://dx.doi.org/10.5564/mjia.v4i0.415 Mongolian Journal of International Affairs Vol.4 2007: 3-20